Brief report: The social responsiveness scale for adults (SRS-A): initial results in a German cohort - Bölte, Sven (Journal of autism and developmental disorders, 2012)
The Social Responsiveness Scale (SRS) is a tool for quantitative autism assessment in children and adolescents. The SRS-A addresses social responsiveness in adulthood. Reliability and validity using the German adaptation of the SRS-A was examined in 20 adults with Autism Spectrum Disorder (ASD), 62 with other mental disorders (CLIN) and 163 typically developing (TD) participants. Cronbach’s alpha ranged from .71 (TD) to .89 (ASD). A SRS-A total score of 67 had a sensitivity of .85, and a speciﬁcity of .83 for ASD versus CLIN/TD. Correlations with established autism scales (ADOS, AQ, SCQ) were moderate to high (r = .25-.83). Results provide adequate preliminary support for the application of the SRS-A.